Transient cognitive impairment in TIA and minor stroke. - Pendlebury, S; Wadling, S; Silver, L; Mehta, Z; Rothwell, P (2011)
BACKGROUND AND PURPOSE: Acute cognitive impairment and delirium occur after major stroke and are associated with poor cognitive outcome. We conducted a population-based study to determine whether transient cognitive impairment (TCI) is seen acutely after cerebral transient ischemic attack (TIA) or minor stroke, and whether it predicts long-term cognitive decline. METHODS: Mini-mental-state examination was performed in consecutive testable patients with TIA or minor stroke (National Institutes of Health Stroke Scale ≤3) seen acutely (1-7 days) in the Oxford Vascular Study (2002-2005) versus after 7 days, and in referrals seen acutely who had a subsequent noncerebrovascular diagnosis. We defined TCI as a baseline Mini-mental-state examination score ≥2 points below the 1-month follow-up score, and identified cognitive impairment (Montreal Cognitive Assessment [MoCA] <26/30) and severe dementia at 1-, 2-, and 5-year follow-up. RESULTS: In 280 TIA and minor stroke patients (mean age/SD 73.5/11.8 years), TCI was more frequent in those seen at 1 to 7 days (80/206; 38.9%) versus later (14/74; 19%; P=0.002) or in noncerebrovascular patients (10/47; 21%; P=0.004). TCI was associated with acute confusion (OR, 5.5; 95% CI, 2.5-11.7; P<0.0001), acute infarct on computed tomography (OR, 2.0; 1.2-3.5; P=0.01), and with residual focal deficits (OR,1.94; 1.13-3.34; P=0.01). However, it was still seen acutely in those whose focal deficits had resolved by time of assessment (41/120; 34%). Although patients with TCI had similar Mini-mental-state examination score by 1 month compared with those without TCI, their 5-year risks of cognitive impairment (OR, 4.3; 1.2-15.7; P=0.03) and severe dementia (OR, 4.9; 1.0-25.8; P=0.05) were increased. CONCLUSIONS: TCI is a manifestation of TIA and minor stroke, and may persist beyond resolution of focal symptoms. Our findings have implications for definitions in TIA and minor stroke and suggest that cognitive fragility may be revealed by minor cerebrovascular events.